Adhesion of PEEK to resin-matrix composites used in dentistry: a short review on surface modification and bond strength. Issue 11 (2nd June 2020) - Escobar, Mario; Henriques, Bruno; Fredel, Márcio C.; Silva, Filipe S.; Özcan, Mutlu; Souza, Júlio C. M.
Abstract: The aim of this work was to perform a scoping review on the PEEK surface modification to establish an effective adhesion to resin-matrix composite for restorative dentistry. A Medline search was performed for related scientific articles published from 1995 up to 2018. PEEK has revealed a low surface energy and a poor wettability that negatively affect the bonding to resin-matrix composites. The increase in roughness by surface modification is the main factor for enhancing mechanical interlocking of PEEK to resin-matrix materials. The highest shear bond strength values of PEEK to resin composites were recorded for gritblasted PEEK modified by sulfuric acid treatment followed by using methacrylate-based adhesives. The combination of ordinary and recent methods for PEEK surface modification has improved PEEK surface for adhesion to resin-matrix materials. Nevertheless, further comparative studies with different adhesive materials and surface treatment are still required.